2020
DOI: 10.1103/physrevb.101.075206
|View full text |Cite
|
Sign up to set email alerts
|

Non-Wiedemann-Franz behavior of the thermal conductivity of organic semiconductors

Abstract: Organic semiconductors have attracted increasing interest as thermoelectric converters in recent years due to their intrinsically low thermal conductivity compared to inorganic materials. This boom has led to encouraging practical results in which the thermal conductivity has predominantly been treated as an empirical number. However, in an optimized thermoelectric material, the electronic component can dominate the thermal conductivity, in which case the figure of merit ZT becomes a function of thermopower an… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
31
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(33 citation statements)
references
References 41 publications
1
31
0
1
Order By: Relevance
“…This suggests that TEG side chains are a promising approach to reduce the thermal conductivity of CPs, a key factor to improve their figure of merit for thermoelectric applications. 44…”
Section: Resultsmentioning
confidence: 99%
“…This suggests that TEG side chains are a promising approach to reduce the thermal conductivity of CPs, a key factor to improve their figure of merit for thermoelectric applications. 44…”
Section: Resultsmentioning
confidence: 99%
“…For metals and highly doped semiconductors, κ e is proportional to the electrical conductivity following the Wiedemann–Franz law, κ e = σ LT , where L is the Lorenz number and T is the temperature. 11 Although in such materials the electrical and vibrational contributions to ZT are inevitably coupled, it cannot be concluded that this relation also holds for doped organic semiconductors. In fact, several studies for PEDOT:PSS, PEDOT:Tos, and doped polyacetylene suggest that the correlation between σ and κ is not yet fully understood.…”
mentioning
confidence: 99%
“… 12 15 Furthermore, a recent theoretical work based on Monte Carlo simulations questioned the validity of the Wiedemann–Franz law in conducting polymers. 16 One of the reasons leading to this ambiguity is, perhaps, that there are few reports that simultaneously address electrical and thermal conduction. 13 , 17 …”
mentioning
confidence: 99%
“…Other interesting routes to explore include the spin Seebeck effect (Sierra et al, 2018) as well as the use of topological states (Xu et al, 2017;Fu et al, 2020) and non-Wiedemann Franz materials (Scheunemann and Kemerink, 2020) that exhibit low electronic thermal conductivity. Compositionally graded materials (Cramer et al, 2018;Ou et al, 2020) can achieve large zTaverage by connecting in series a composition with high-performance at high temperatures with a composition with high-performance at low temperatures.…”
Section: P R O V I S I O N a Lmentioning
confidence: 99%